EMPOWERMENT OF DAIRY CATTLE FARMERS IN THE AREAS SELINGKAR WILIS THROUGH COMMUNITY SERVICE’S POSTGRADUATE SCHOOL: PEMBERDAYAAN PETERNAK SAPI PERAH DI SELINGKAR WILIS, PENGABDIAN KEPADA MASYARAKAT SEKOLAH PASCASARJANA - Yuliani, M. Gandul Atik; Madyawati, Sri Pantja; Hariyono, Hariyono (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: The Postgraduate School strives to establish itself as a world-class institution with a significant global impact. To achieve this vision, it has forged partnerships with regional leaders, emphasizing community service. Our latest initiative,